PENGARUH PEMBERIAN KOTORAN BEBEK DAN POC SAYURAN PADA PERTUMBUHAN DAN PRODUKSI TOMAT BUAH ( Solanum lycopersicum L. ) - Sembiring, Gery Tarindo; Ate Tarigan, Ruth Riah; Siregar, Maimunah (Agros Journal of Agriculture Science, 2024)
The aim of this research was to determine the effect of applying duck manure and liquid organic vegetable fertilizer on the growth and production of tomato plants. This research used a factorial randomized block design (RAK) consisting of 2 factors with 12 treatment combinations and 3 replications so that 36 plots were required in the study. The first factor examined was the treatment of duck manure with the symbol "K" consisting of K0 = 0 g/polybag, K1 = 500 g/polybag, K2 = 1000 g/polybag, K3 = 1500 g/polybag. Factor II treatment of giving liquid organic vegetable fertilizer with the symbol S consists of S0 = 0 mL/liter of water/plot, S1 = 10 mL/liter of water/plot, S2 = 20 mL/liter of water/plot. The parameters observed were plant height (cm), stem diameter (mm), number of productive branches, number of fruit per sample, weight of fruit per sample (g) and fruit diameter (mm). The results of the research showed that the application of duck dung fertilizer showed a very significant different effect on the parameters of plant height (cm), stem diameter (mm), sample fruit weight (g) and fruit diameter (mm), but showed no significant effect on the parameter of the number of productive branches. , number of fruit per sample, while liquid organic fertilizer for vegetables and the second interaction showed no significant influence on all observation parameters, namely plant height (cm), stem diameter (mm), number of productive branches, number of fruit per sample, weight of fruit per sample (g) and fruit diameter (mm). Key words: duck manure, liquid organic vegetable fertilizer, tomatoes